Audit and risk committee in financial crime prevention. Issue 1 (7th January 2019) - Abdullah, Wan Nailah; Said, Roshima
Abstract : Purpose: This empirical study aims to examine two areas: first, the characteristics of the audit committee and their relationship with corporate financial crime so as to ensure that their effectiveness as a corporate governance mechanism is still relevant; and second, the effectiveness of having a risk committee which is separated from the audit committee in the prevention of corporate financial crime. Design/methodology/approach: This empirical research was carried out by using a Web-based data collection for corporate financial crime cases. Findings: While the results for audit committee characteristics are not supported, the findings, however, indicate a significant relationship between the existence of a stand-alone risk committee with corporate financial crime incidences. Practical implications: The result of the study serves as an empirical indicator of a firm's consideration in deciding on the implementation of a stand-alone risk committee from its audit committee. Originality/value: Both the descriptive and correlation analyses produced by this paper provide new insights into the extent of corporate financial crime, as well as the empirical evidence of the effectiveness of having a stand-alone risk committee.